Advancing prosociality in extended reality: systematic review of the use of embodied virtual agents to trigger prosocial behaviour in extended reality - Yousefi, Mamehgol; Crowe, Stephanie Elena; Hoermann, Simon; Sharifi, Mos; Romera, Alvaro; Shahi, Ahmad; Piumsomboon, Thammathip (Frontiers in Virtual Reality, 2024)
Attention has increasingly been focused on the potential of Extended Reality (XR) and Embodied Virtual Agents (EVAs) to significantly influence human behaviour. While an expanding body of literature explores the individual impacts of XR and EVAs, there is a noticeable gap in the literature regarding their combined influence on eliciting prosocial behaviour in humans. The purpose of this systematic review is to explore this intersection, offering insights into their multifaceted effects on human prosocial behaviour and the implications for future research and development of EVAs in XR. Our systematic review adopted a scoping approach due to the limited number of studies directly focused on EVAs (i.e., autonomously computer-controlled entities). Despite this, we observed the use of various forms of virtual characters (VCs) to elicit prosocial behaviour. An in-depth analysis of 15 selected studies indicates complex patterns in how XR and VCs affect users' prosocial behaviour and interactions. Our review suggests that there is promising potential for EVAs to promote prosocial behaviour. However, further research is necessary to identify the design and interaction-related attributes that enhance the effectiveness of these technologies, particularly for socially interactive EVAs in XR environments.